Fire history in arid and semi-arid regions of northwest China during the last glacial period inferred from a charcoal record in Hetao Basin. - Siwei Liu; Xinling Li; Shengrui Zhang; Maotang Cai; Xinyu He; Siyu Li; Peixin Ma (PLoS ONE)
In arid and semi-arid regions of northwest China, the ecological environment is fragile and fire occurs frequently. Fire has an important impact on the regional ecological environment. The last glacial period is the most recent glacial period, and the climate is unstable, characterized by millennial oscillations. The research reveals regional fire evolution and driving mechanism of the last glacial period in arid and semi-arid regions of northwest China. The research can provide important theoretical reference for regional fire prevention and control in the future. Therefore, a sediment core was drilled from the southwestern part of the Hetao Basin. In this study, we extended the study sequence to 23.68-m-long, and reconstructed the history of fire during the last glacial period (MIS4 ~ MIS2). The results are as follows: (1) 72.2 ~ 59.5 ka BP: The regional fire activity was low. 59.5 ~ 49.8 ka BP: The regional fire activity was relatively higher than the previous stage. 49.8 ~ 36.9 ka BP: The regional fire activity had little change than the previous stage. 36.9 ~ 26.6 ka BP: The regional fire activity was relatively higher than the previous stage. 26.6 ~ 18.9 ka BP: The regional fire activity was relatively lower than the previous stage. 18.9 ~ 15.7 ka BP: The regional fire activity was low. (2) The regional fire activity was low during the Heinrich events in the Hetao Basin. (3) The more fire activity in the last glacial period in the Hetao Basin was due to the warm and wet climatic conditions, which promoted better regional vegetation development and increased regional biomass, which provided sufficient fuel for the occurrence of fire activity.